2007
DOI: 10.1158/0008-5472.can-06-1476
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Apoptosis and Increased Deletion Mutations at Aprt Locus In vivo in Mice Exposed to Repeated Ionizing Radiation

Abstract: Exposure to ionizing radiation (IR) is a risk factor for carcinogenesis because it is a mutagen. However, a single 4-Gy whole body X-ray exposure only induced a modest increase of mutations at the Aprt reporter gene locus in mouse T cells. Intriguingly, when the same dose of IR was given in a fractionated protocol (1 Gy  4 at weekly intervals), there was a strong induction of Aprt mutations in T cells. Many of these were mutations that arose via interstitial deletions inclusive of Aprt or by intragenic deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
1
24
1
Order By: Relevance
“…Expression of the RAD51 gene was measured with a quantitative real-time polymerase chain reaction (PCR) assay as previously reported [38]. Expression level was calculated as a ratio of the mRNA level for a given gene relative to the mRNA level for glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the RAD51 gene was measured with a quantitative real-time polymerase chain reaction (PCR) assay as previously reported [38]. Expression level was calculated as a ratio of the mRNA level for a given gene relative to the mRNA level for glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…Nuclear protein extracts were prepared as described [38]. Equivalent concentrations of nuclear extracts were electrophoresed with sodium dodecyl sulfate-polyacrylamide gel electrophoresis gels and transferred onto polyvinylidene difluoride membranes.…”
Section: Immunoblottingmentioning
confidence: 99%
“…The occurrence of dosedependent radiation mutagenesis in mice has been demonstrated in a number of studies [Dempsey and Morley 1986;Lorenz et al, 1990Lorenz et al, , 1993Lorenz et al, , 1994Grdina et al, 1992;Kataoka et al, 1992Kataoka et al, , 1993Gaziev et al, 1995;Klarmann et al, 1995;Dobrovolsky et al, 2002;Liang et al, 2007]. However, the more extensive evaluation of time elapsed after acute g irradiation revealed that mutant frequency dependence on dose shifted between 3 and 5 weeks and 10-53 weeks, from being clearly quadratic at the peak of mutant recovery in weeks 3-5 to a statistically strong but less-defined dose relationship in the later time frame.…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification of Hprt indicated that intragenic deletions in Hprt were significantly induced by X-irradiation (Nguyen, Liang and Tischfield, unpublished data). Molecular analyses of Aprt mutants also demonstrated that intragenic alterations in Aprt (base substitutions and deletions) but not large chromosome alterations were induced by 1 Gy X-ray [8]. However, the putative induction in intragenic alterations (3.2 × 10 −6 ) at Aprt was not enough to produce a significant increase in overall Aprt MF due to the high spontaneous Aprt MF (24 × 10 −6 ).…”
Section: Prenatal X-irradiation Increases the Aprt But Not The Hprt Mmentioning
confidence: 98%
“…Specifically, 1 Gy X-ray increased the Hprt MF by 3.3-fold as compared to unirradiated controls (11 × 10 −6 v.s. 3.3 × 10 −6 , in irradiated mice and controls, respectively) [8]. PCR amplification of Hprt indicated that intragenic deletions in Hprt were significantly induced by X-irradiation (Nguyen, Liang and Tischfield, unpublished data).…”
Section: Prenatal X-irradiation Increases the Aprt But Not The Hprt Mmentioning
confidence: 98%